ON THE QUESTION OF THE STATE AND PROSPECTS OF RESEARCH OF THE PROBLEM OF THE ANTI-JEWISH POGROM MOVEMENT ON THE TERRITORY OF UKRAINE IN 1917–1921. - LAZAROVYCH, Mykola (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The state of the research of the problem of Jewish massacre on the territory of Ukraine during the National Liberation Struggle of 1917–1921 is analyzed. This issue is extremely difficult to study because it is caused by a set of historical stereotypes, socio-economic contradictions and antagonisms. That is why it must be considered in the context of difficult objective circumstances that developed in one of the most critical periods of Ukrainian history. The aim of the article is to analyze and systematize the historiography of the problem of the anti-Jewish pogrom movement on the territory of Ukraine in 1917–1921. It is necessary to study the scientific works deal with the causes and preconditions of the Jewish massacres in Ukraine, their consequences and forces involved in the massacre movement, the main rule-making and institutional measures taken by government agencies to ensure the right to life. Analysis of the source base of the study showed a growing interest of scientists in studying the outlined problem. It is represented by a significant number of works, mostly articles, which to a greater or lesser extent reveal a number of aspects of this complex phenomenon. The attitude of the Ukrainian authorities to the Jewish massacres was negative. Thay made attempts to fight this evil by all available means, in particular by providing rule-making and institutional support for the problem, the use of military force and the introduction of various punishments, including the death penalty, for rioters, providing material assistance to victims, and so on. The effectiveness of such actions, although determined by the difficult conditions of wartime and anarchy, still provided positive results. The main conclusion of the analysis of the outlined tragic events is the realization that all national conflicts that arise between peoples, their groups or individuals must be resolved through negotiations and mutual compromises. Taking to concideration to this, only the formation of an effective concept of state ethnopolitics will ensure a harmonious combination of the interests of the titular nation and the non-ethnic population. Prospects for further research of the problem of the anti-Jewish massacre movement in Ukraine in 1917–1921 are that they should be analyzed from the point of view of today. After all, both then and now Russia seeks to influence Ukraine in various ways, using large-scale misinformation, outright lies, falsification of facts, and defamation of Ukrainian statehood before the world.